Ternary carbon aerogel for efficiently removing 4-nitrophenol and preparation method thereof

By preparing ternary carbon aerogel materials, the problem of difficult removal of 4-nitrophenol from industrial wastewater was solved, achieving efficient removal and environmentally friendly treatment results.

CN119524863APending Publication Date: 2025-02-28SHENYANG JIANZHU UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411676001.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

4-Nitrophenol is difficult to remove efficiently from industrial wastewater, and existing methods may cause secondary environmental pollution.

Method used

Ternary carbon aerogels were prepared by freeze-drying and pyrolysis. Agarose AG was co-doped with metal-organic framework material FFPBA and Ce to form FFPBA-C/AG-CA-Ce material, which was used to catalyze the degradation of 4-nitrophenol by potassium persulfate.

Benefits of technology

The prepared ternary carbon aerogel has good mechanical strength and catalytic activity, can efficiently remove 4-nitrophenol, is easy to recycle, and will not cause secondary pollution to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524863A_ABST
    Figure CN119524863A_ABST
Patent Text Reader

Abstract

The invention relates to a ternary carbon aerogel for efficiently removing 4-nitrophenol and a preparation method thereof, the method comprises the following steps: dispersing FFPBA nanoparticles into deionized water, adding agarose, and stirring in a water bath until the FFPBA nanoparticles and the agarose are uniformly mixed; freezing the obtained mixed solution, and treating the mixed solution by using a freeze dryer under a vacuum condition to obtain FFPBA / AG aerogel; then carrying out pyrolysis in a nitrogen atmosphere, so as to obtain FFPBA / AG-CA carbon aerogel; and finally, soaking the FFPBA / AG-CA carbon aerogel into a cerous nitrate solution, and performing pyrolysis under the condition of 60 DEG C until the liquid is completely volatilized in a nitrogen atmosphere to obtain the FFPBA-C / AG-CA-Ce carbon aerogel material. The carbon aerogel has good mechanical strength, has excellent catalytic activity on degradation of 4-nitrophenol by potassium hydrogen persulfate, is easy to recover, and does not cause secondary pollution to the environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of environmental nanomaterials, in particular to a ternary carbon aerogel for efficiently removing 4-nitrophenol and a preparation method thereof. Background Art

[0002] Industrial wastewater is considered to be one of the difficult-to-treat water bodies due to its complex composition, high toxicity, and difficulty in treatment. It is estimated that by the end of 2050, the water demand of the industrial production sector will occupy a quarter of the global freshwater resources. The wastewater discharged by various industries is estimated to be 360 ​​billion square meters per year, which will increase by 51% by the end of 2050. The wastewater produced by different industries has different components. If the treatment level is not up to standard, it may damage the aquatic ecosystem. The treatment of wastewater requires economic support and advanced facilities to assist. Nitro compounds have attracted much attention due to their toxicity, difficulty in degradation, and easy accumulation. Among them, 4-nitrophenol (4-NP) is widely used in life as an intermediate in the industrial production of Chinese medicine, leather, dyes and other chemicals. It has been identified as a non-biodegradable pollutant by the US Environmental Protection Agency (EPA). If 4-NP is not treated in time, it will cause serious damage to the aquatic ecosystem. Therefore, it is urgent to find a suitable method to degrade 4-NP. Summary of the invention

[0003] To solve the above problems, the purpose of the present invention is to provide a ternary carbon aerogel for efficient removal of 4-nitrophenol and a preparation method thereof, mainly through freeze drying technology and pyrolysis technology, metal organic framework material (MOFs) FFPBA and Ce co-doped, mixed with agarose (AG) to prepare a ternary symbiotic carbon aerogel (FFPBA-C / AG-CA-Ce). The carbon aerogel has good mechanical strength, excellent catalytic activity, can efficiently remove 4-nitrophenol, and is easy to recycle without causing secondary pollution to the environment.

[0004] A method for preparing a ternary carbon aerogel for efficient removal of 4-nitrophenol, specifically comprising the following steps:

[0005] (1) Preparation of FFPBA nanoparticles;

[0006] (2) Dispersing FFPBA nanoparticles in deionized water, then adding agarose (AG), stirring in a 65°C water bath until the mixture is uniformly mixed to obtain a mixed solution;

[0007] (3) freezing the mixed solution obtained in step (2), and then treating it with a freeze dryer under vacuum conditions to obtain FFPBA / AG aerogel;

[0008] (4) pyrolyzing the FFPBA / AG aerogel obtained in step (3) under a nitrogen atmosphere to obtain a FFPBA / AG-CA carbon aerogel;

[0009] (5) Immerse the FFPBA / AG-CA carbon aerogel obtained in step (4) in a cerium nitrate solution, wait for the liquid to completely evaporate at 60° C., and then pyrolyze the FFPBA / AG-CA-Ce in a nitrogen atmosphere to finally obtain the FFPBA-C / AG-CA-Ce carbon aerogel material, i.e., the ternary carbon aerogel.

[0010] Furthermore, the preparation of FFPBA nanoparticles in step (1) is as follows: 15.2 g of polyvinyl pyrrolidone (PVP) is placed in 200 mL of deionized water, and after it is completely dissolved, 1.8 mL of concentrated hydrochloric acid is added and stirred for 10 min to obtain solution A; 0.44 g of K 4 [Fe(CN) 6 ]·3H 2 O was added to solution A and stirred for 5 min to obtain a mixed solution; the mixed solution was poured into a reactor lined with polytetrafluoroethylene (PTFE), heated at 80° C. for 24 h for hydrothermal reaction, and naturally cooled after the heating to obtain a Fe-FePBA mixed solution; the Fe-FePBA mixed solution was centrifuged to achieve solid-liquid separation, the upper layer of liquid was discarded, and the obtained solid was washed with deionized water and anhydrous ethanol for 3 times to obtain Fe-FePBA nanoparticles, i.e., FFPBA nanoparticles;

[0011] Furthermore, in step (2), ultrasound is used to disperse the FFPBA nanoparticles into deionized water.

[0012] Wherein, step (2) is carried out at room temperature.

[0013] Furthermore, in step (4), the pyrolysis is carried out at 800-900° C. for 3 h.

[0014] Furthermore, in step (5), the pyrolysis is carried out at 800-900° C. for 3 h.

[0015] Furthermore, the concentration of the cerium nitrate solution in step (5) is 25 mM; complete evaporation of the liquid means that the material is dried to be free of moisture and is obviously in a dry state when observed with the naked eye, that is, the material will appear lumpy due to loss of moisture.

[0016] The present invention also provides a ternary carbon aerogel for efficiently removing 4-nitrophenol obtained according to the preparation method and application of the ternary carbon aerogel in removing 4-nitrophenol.

[0017] Furthermore, the application of the ternary carbon aerogel in the removal of 4-nitrophenol is to add the ternary carbon aerogel (i.e., FFPBA-C / AG-CA-Ce carbon aerogel material) and potassium persulfate (PMS) to a solution containing 4-nitrophenol for reaction, and the ternary carbon aerogel is used to catalyze the degradation of 4-nitrophenol by potassium persulfate.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The preparation method of the present invention is simpler and faster. Most importantly, the agarose used is a biomass material, which can better adapt to environmental changes and show better adaptability in different environments. The composite material finally synthesized not only has good mechanical strength and excellent catalytic activity, can efficiently remove 4-nitrophenol, but also is easy to recycle and will not cause secondary pollution to the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic diagram of the process for preparing FFPBA-C / AG-CA-Ce in Example 1 of the present invention;

[0021] Figure 2 This is a photo of FFPBA-C / AG-CA-Ce prepared in Example 1;

[0022] Figure 3 They are the scanning electron micrographs of FFPBA, FFPBA / AG-CA, and FFPBA-C / AG-CA-Ce, respectively. From left to right in the figure, they correspond to FFPBA, FFPBA / AG-CA, and FFPBA-C / AG-CA-Ce;

[0023] Figure 4 X-ray diffraction pattern of FFPBA-C / AG-CA-Ce prepared in Example 1;

[0024] Figure 5 This is an experiment on the catalytic degradation of 10 mg / L 4-nitrophenol by FFPBA, FFPBA / AG, FFPBA / AG-CA, FFPBA / AG-CA-Ce, and FFPBA-C / AG-CA-Ce. DETAILED DESCRIPTION

[0025] In order to better understand the content of the present invention, the present invention will be further described below in conjunction with specific embodiments and drawings. The following embodiments are implemented based on the technology of the present invention, and detailed implementation methods and operating steps are given, but the protection scope of the present invention is not limited to the following embodiments.

[0026] Embodiment 1:

[0027] (1) 15.2 g of polyvinyl pyrrolidone (PVP) was placed in 200 mL of deionized water. After it was completely dissolved, 1.8 mL of concentrated hydrochloric acid was added and stirred for 10 min to obtain solution A. 0.44 g of K 4 [Fe(CN) 6 ]·3H 2 O was added to solution A and stirred for 5 min to obtain a mixed solution; the mixed solution was poured into a reactor lined with polytetrafluoroethylene (PTFE), heated at 80° C. for 24 h for hydrothermal reaction, and naturally cooled after the heating to obtain a Fe-FePBA mixed solution; the Fe-FePBA mixed solution was centrifuged to achieve solid-liquid separation, the upper layer of liquid was discarded, and the obtained solid was washed with deionized water and anhydrous ethanol for 3 times to obtain Fe-FePBA nanoparticles, i.e., FFPBA nanoparticles;

[0028] (2) 0.4 g of FFPBA nanoparticles were added to 20 mL of deionized water, and dispersed by ultrasound. Then, 0.4 g of agarose (AG) was added, and stirred in a 65° C. water bath until the mixture was uniformly mixed to obtain a mixed solution;

[0029] (3) placing the mixed solution obtained in step (2) into a freezer for 8 h, and then placing it into a freeze dryer for two days under vacuum conditions to obtain FFPBA / AG aerogel;

[0030] (4) Under a nitrogen atmosphere, the FFPBA / AG aerogel obtained in step (3) was pyrolyzed at 900° C. for 3 h to obtain a FFPBA / AG-CA carbon aerogel;

[0031] (5) The FFPBA / AG-CA carbon aerogel obtained in step (4) was immersed in 60 mL of 25 mM cerium nitrate solution at 60°C, and the liquid was allowed to completely evaporate. When the material was completely dry, FFPBA / AG-CA-Ce was obtained. Then, the FFPBA / AG-CA-Ce was pyrolyzed at 800°C for 3 h in a nitrogen atmosphere to finally obtain FFPBA-C / AG-CA-Ce carbon aerogel material.

[0032] Embodiment 2:

[0033] (1) 15.2 g of polyvinyl pyrrolidone (PVP) was placed in 200 mL of deionized water. After it was completely dissolved, 1.8 mL of concentrated hydrochloric acid was added and stirred for 10 min to obtain solution A. 0.44 g of K 4 [Fe(CN) 6 ]·3H 2O was added to solution A and stirred for 5 min to obtain a mixed solution; the mixed solution was poured into a reactor lined with polytetrafluoroethylene (PTFE), heated at 80° C. for 24 h for hydrothermal reaction, and naturally cooled after the heating to obtain a Fe-FePBA mixed solution; the Fe-FePBA mixed solution was centrifuged to achieve solid-liquid separation, the upper layer of liquid was discarded, and the obtained solid was washed with deionized water and anhydrous ethanol for 3 times to obtain Fe-FePBA nanoparticles, i.e., FFPBA nanoparticles;

[0034] (2) 0.8 g of FFPBA nanoparticles were added to 40 mL of deionized water, and dispersed by ultrasound. Then, 0.8 g of agarose (AG) was added, and stirred in a 65° C. water bath until the mixture was uniformly mixed to obtain a mixed solution;

[0035] (3) placing the mixed solution obtained in step (2) into a freezer for 8 h, and then placing it into a freeze dryer and treating it under vacuum conditions for two days to obtain FFPBA / AG aerogel;

[0036] (4) Under a nitrogen atmosphere, the FFPBA / AG aerogel obtained in step (3) was pyrolyzed at 900° C. for 3 h to obtain a FFPBA / AG-CA carbon aerogel;

[0037] (5) The FFPBA / AG-CA carbon aerogel obtained in step (4) was immersed in 120 mL of 25 mM cerium nitrate solution at 60°C, and the liquid was completely evaporated. When the material was in a completely dry state, FFPBA / AG-CA-Ce was obtained. Then, the FFPBA / AG-CA-Ce was pyrolyzed at 900°C for 3 h in a nitrogen atmosphere to finally obtain FFPBA-C / AG-CA-Ce carbon aerogel material.

[0038] Embodiment 3:

[0039] (1) 15.2 g of polyvinyl pyrrolidone (PVP) was placed in 200 mL of deionized water. After it was completely dissolved, 1.8 mL of concentrated hydrochloric acid was added and stirred for 10 min to obtain solution A. 0.44 g of K 4 [Fe(CN) 6 ]·3H 2 O was added to solution A and stirred for 5 min to obtain a mixed solution; the mixed solution was poured into a reactor lined with polytetrafluoroethylene (PTFE), heated at 80° C. for 24 h for hydrothermal reaction, and naturally cooled after the heating to obtain a Fe-FePBA mixed solution; the Fe-FePBA mixed solution was centrifuged to achieve solid-liquid separation, the upper layer of liquid was discarded, and the obtained solid was washed with deionized water and anhydrous ethanol for 3 times to obtain Fe-FePBA nanoparticles, i.e., FFPBA nanoparticles;

[0040] (2) adding 2.0 g of FFPBA nanoparticles to 100 mL of deionized water, dispersing them by ultrasound, then adding 2.0 g of agarose (AG), stirring in a 65° C. water bath until the mixture is uniformly mixed, to obtain a mixed solution;

[0041] (3) placing the mixed solution obtained in step (2) into a freezer for 8 h, and then placing it into a freeze dryer and treating it under vacuum conditions for two days to obtain FFPBA / AG aerogel;

[0042] (4) Under a nitrogen atmosphere, the FFPBA / AG aerogel obtained in step (3) was pyrolyzed at 800° C. for 3 h to obtain FFPBA / AG-CA carbon aerogel;

[0043] (5) The FFPBA / AG-CA carbon aerogel obtained in step (4) was immersed in 300 mL of 25 mM cerium nitrate solution at 60°C, and the liquid was completely evaporated until the material was in a completely dry state to obtain FFPBA / AG-CA-Ce. Then, the solid obtained after the liquid evaporated was pyrolyzed at 800°C for 3 h in a nitrogen atmosphere to finally obtain FFPBA-C / AG-CA-Ce carbon aerogel material.

[0044] The schematic diagram of the process for preparing FFPBA-C / AG-CA-Ce of the present invention is as follows Figure 1 shown.

[0045] Figure 2 This is a photo of FFPBA-C / AG-CA-Ce prepared in Example 1. Figure 2 It can be seen that the material has a certain mechanical strength.

[0046] Figure 3 The scanning electron micrographs of FFPBA, FFPBA / AG-CA, and FFPBA-C / AG-CA-Ce are shown in Figure 1. From left to right, they correspond to FFPBA, FFPBA / AG-CA, and FFPBA-C / AG-CA-Ce. Figure 3 It can be seen that the morphology of FFPBA, the surface state after being made into carbon aerogel, and the material condition after being doped with Ce and carbonized, among which FFPBA is a tetrahedron.

[0047] Figure 4 is the X-ray diffraction pattern of FFPBA-C / AG-CA-Ce prepared in Example 1; Figure 4 It can be seen that Ce is perfectly loaded onto the carbon aerogel.

[0048] Application Example 1

[0049] The FFPBA-C / AG-CA-Ce carbon aerogel material prepared in Example 1 was used to catalyze the degradation of 4-nitrophenol by potassium persulfate (PMS).

[0050] (1) Take 100 mL of 10 mg / L 4-nitrophenol aqueous solution;

[0051] (2) 20 mg of FFPBA-C / AG-CA-Ce prepared in Example 1 and 20 mg of PMS were added to the above 4-nitrophenol solution, respectively, and stirred for reaction at 25° C.;

[0052] (3) Sampling was performed at the time points of 0 min, 2 min, 4 min, 6 min, 10 min, 15 min, 20 min, 30 min, 40 min, 50 min, and 60 min, and the UV absorption spectrum of the sampled solution was obtained. The concentration of the corresponding solution was obtained according to the UV absorption spectrum, and then the concentration ratio C / C was calculated. 0 The curve (C 0 is the initial concentration of 4-nitrophenol, C is the concentration of 4-nitrophenol at time t), wherein 0 min refers to the time when FFPBA-C / AG-CA-Ce and 20 mg PMS are not added, that is, the sample taken at 0 min is the 4-nitrophenol aqueous solution in step (1), and the sample taken at 2 min refers to the solution taken after adding FFPBA-C / AG-CA-Ce and 20 mg PMS and stirring for 2 min, and the same applies to other time points.

[0053] The above catalytic degradation method was used to replace FFPBA-C / AG-CA-Ce with FFPBA nanoparticles prepared by the preparation method of step (1) in Example 1, FFPBA / AG aerogel prepared by the preparation method of step (3), FFPBA / AG-CA carbon aerogel prepared by the preparation method of step (4), and FFPBA / AG-CA-Ce prepared by the preparation method of step (5), respectively. The other methods were the same as above. The results were as follows: Figure 5 As shown. Figure 5 It can be seen that the carbon aerogel introduced with Ce has very excellent catalytic activity. The above results prove that when using FFPBA-C / AG-CA-Ce carbon aerogel material, the removal rate of 4-nitrophenol is as high as 90%, indicating that FFPBA-C / AG-CA-Ce carbon aerogel material can efficiently catalyze PMS, has good catalytic activity, and has very efficient degradation performance for 4-nitrophenol, proving that it has good prospects in degrading 4-nitrophenol in water.

[0054] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a ternary carbon aerogel for efficient removal of 4-nitrophenol, characterized in that: The specific steps include: (1) preparing FFPBA nanoparticles; (2) Dispersing FFPBA nanoparticles in deionized water, then adding agarose, stirring in a 65°C water bath until the mixture is uniformly mixed to obtain a mixed solution; (3) freezing the mixed solution obtained in step (2), and then treating it with a freeze dryer under vacuum conditions to obtain FFPBA / AG aerogel; (4) pyrolyzing the FFPBA / AG aerogel obtained in step (3) under a nitrogen atmosphere to obtain a FFPBA / AG-CA carbon aerogel; (5) Immerse the FFPBA / AG-CA carbon aerogel obtained in step (4) in a cerium nitrate solution, wait for the liquid to completely evaporate at 60° C., and then pyrolyze the FFPBA / AG-CA-Ce in a nitrogen atmosphere to finally obtain the FFPBA-C / AG-CA-Ce carbon aerogel material, i.e., the ternary carbon aerogel.

2. The method for preparing the ternary carbon aerogel for efficient removal of 4-nitrophenol according to claim 1, characterized in that: The preparation of FFPBA nanoparticles in step (1) is as follows: 15.2 g of polyvinyl pyrrolidone (PVP) is placed in 200 mL of deionized water, and after it is completely dissolved, 1.8 mL of concentrated hydrochloric acid is added, and the mixture is stirred for 10 min to obtain solution A; 0.44 g of K4[Fe(CN)6]·3H2O is added to solution A and stirred for 5 min to obtain a mixed solution; the mixed solution is poured into a reactor lined with polytetrafluoroethylene (PTFE), heated at 80° C. for 24 h for hydrothermal reaction, and naturally cooled after heating to obtain a Fe-FePBA mixed solution; the Fe-FePBA mixed solution is centrifuged to achieve solid-liquid separation, the upper liquid is discarded, and the obtained solid is washed 3 times with deionized water and anhydrous ethanol to obtain Fe-FePBA nanoparticles, i.e., FFPBA nanoparticles.

3. The method for preparing the ternary carbon aerogel for efficient removal of 4-nitrophenol according to claim 1, characterized in that: In step (2), ultrasound is used to disperse the FFPBA nanoparticles into deionized water.

4. The method for preparing the ternary carbon aerogel for efficient removal of 4-nitrophenol according to claim 1, characterized in that: In step (4), the pyrolysis is carried out at 800-900° C. for 3 h.

5. The method for preparing the ternary carbon aerogel for efficient removal of 4-nitrophenol according to claim 1, characterized in that: The concentration of the cerium nitrate solution in step (5) is 25 mM.

6. The method for preparing the ternary carbon aerogel for efficient removal of 4-nitrophenol as claimed in claim 1, characterized in that In step (5), the pyrolysis is carried out at 800-900° C. for 3 h.

7. The ternary carbon aerogel for efficient removal of 4-nitrophenol obtained by the preparation method according to any one of claims 1 to 6.

8. Use of the ternary carbon aerogel for efficient removal of 4-nitrophenol as claimed in claim 7 in the removal of 4-nitrophenol.

9. The use according to claim 8, characterized in that The ternary carbon aerogel and potassium persulfate are respectively added into a solution containing 4-nitrophenol to carry out a reaction, and the ternary carbon aerogel is used for catalyzing potassium persulfate to degrade 4-nitrophenol.

Citation Information

Cited By

  • Preparation method of carbon aerogel for efficiently removing nitrophenol

    CN116986576A